"F*ck off Google": protest against Google Campus Berlin. Issue 6 (30th March 2019) - Fritze, Martin Paul; Gänser-Stickler, Gertraud Maria; Türk, Sarah; Zhao, Yingshuai
Abstract : Theoretical basis: This case applies a stakeholder analysis to examine the trade-offs between the firm's strategy and the interests of different stakeholder groups. A PESTEL analysis supports an evaluation of the firm's situation. Consumer behavior theories on psychological ownership and territoriality offer a framework for analyzing the conflicts that arise from the inhabitants' protests. Research methodology: This case relies on secondary sources, including news reports, social media sites and company websites. This case has been classroom tested with undergraduate students in a strategic management course in January 2019 at the University of Cologne, Germany. Case overview/synopsis: In November 2016, Google announced its intentions to rent a building in the Kreuzberg district of Berlin to open a Google Campus, a business incubator for tech start-ups that would offer entrepreneurs support, workshops and access to networks. Following the announcement, dissatisfied local communities organized protests, in which leaders complained that "It is extremely violent and arrogant of this mega-corporation, whose business model is based on mass surveillance and which speculates like crazy, to set up shop here" ( Business Times, 2018). Berlin's Government supported the Google Campus plan; inhabitants rejected it with fierce and persistent protests. In face of this challenge, was it still possible for Google to continue its plans in Berlin? Complexity academic level: This case qualifies for use in strategic management classes at undergraduate and MBA levels. Its focus aligns well with stakeholder analyses, PESTEL analyses and business strategy. In addition, for courses on organizational communications or public relations, this case provides a way to explore the relationship between Google and its stakeholders, especially protesters, in detail. Moreover, this case is well suited for consumer research and public policy courses (e.g., transformative consumer research) centered on discussions of territoriality.